An energy-efficient method for mitigating membrane fouling: A novel embodiment of the inverse fluidized bed. Issue 4 (4th March 2018) - Zamani, Farhad; Ma, Aijing; Han, Qi; Ma, Qinglang; Zhang, Hua; Fane, Anthony G.; Chew, Jia Wei
ABSTRACT: A novel inverse fluidized bed (IFB) was developed to improve membrane fouling mitigation vis-à-vis the conventional aeration method. The fluidized media, whose density was less than water and oleophilic, were more effective than bubbles for both feeds containing oil and particulates due to their greater inertia. The key highlights are (i) for all the conditions investigated, IFB consistently gave a lower trans-membrane pressure (TMP) than aeration at the same energy requirement; (ii) IFB performed better even when the energy input was reduced by 87.5%; (iii) IFB provided an impressive enhancement of up to 54 times that of dead-end filtration.